The Effect of a Combination of Short Wave Diathermy and Dynamic Stretching on Pain Values in Cases of Myogenic Low Back Pain Employees at Menur Mental Hospital, Surabaya - Arie Wicaksono; Achmad Fariz; Nurul Halimah; Angrita Pradita (Jurnal EduHealth, 2023)
This study aims to evaluate the impact of a combination of Short Wave Diathermy (SWD) and Dynamic Stretching therapy on pain levels in cases of myogenic Low Back Pain (LBP) in employees at Menur Mental Hospital, Surabaya. This study involved the participation of a group of employees who suffered from myogenic LBP and were divided into a control group and an intervention group. The intervention group received a combination of SWD therapy and Dynamic Stretching exercise sessions, while the control group did not receive any intervention other than standard care. Evaluation was carried out using the pain scale assessment method before the intervention, after the intervention, and at the next follow-up. Results showed that the combination of SWD and Dynamic Stretching resulted in a significant reduction in pain scores compared to the control group. These findings highlight the potential effectiveness of this combined therapy in managing pain in cases of myogenic LBP, providing a basis for further understanding regarding the use of this combined therapy in the treatment of similar conditions.